The effectiveness of varying of Tideglusib gel concentrations in ridge preservation of osteoporotic models - Habba, Doaa Adel; Ahmed, Omneya E.; Abdelfatah, Heba (South Eastern European Journal of Public Health, 2025)
Background: Repairing impaired hard tissues in osteoporotic patients posed challenges with restricted treatment modalities. Meanwhile, Tideglusib is regarded as an exciting treatment for Alzheimer's disease; its applications for ridge preservation in osteoporotic rabbits are not investigated. The aim of this research was to investigate the effects of Tideglusib gel in osteoporotic rabbits with empty sockets. Thirty-two male rabbits weighing 2.5 - 3 kg were used for the study. Then the mandibular first molar of each rabbit was extracted. The rabbits were allocated into 4 study groups: 1. Control normal rabbit with socket healed normally; 2. Osteoporotic rabbit with socket healed normally; 3. Osteoporotic rabbit with socket received 5 μM Tideglusib gel; 4. Osteoporotic rabbit with socket received 10 μM Tideglusib gel. At four weeks, the rabbits were then slaughtered. To assess the bone development in the extraction sockets, histopathologic and histomorphometeric analysis were carried out. Results: After 4 weeks of socket augmentation, a significant increase in mean % of mature bone (MB) in the control group and two treated groups. While Group 2 showed the significantly lowest mean % increase in MB. Also, a significantly mean % increase of collagen deposition was generated in all study groups. However, group 2 showed the statistically significantly lowest mean % increase. Group 4 demonstrated significantly higher new bone formation than those of groups 2 and 3. Conclusion: Tideglusib gel could accelerate bone healing through an increase in the trabecular area and elevate collagen deposition in the extracted socket of a rabbit. A specific dose-dependent response of Tideglusib gel was observed in histological and morphometric parameters, indicating that 10 μM of Tideglusib gel is considered an effective rational therapy for post-extraction socket repair, particularly in the osteoporotic model.